Volume 10C: Turbomachinery — Design Methods and CFD Modeling for Turbomachinery; Ducts, Noise, and Component Interactions 2022
DOI: 10.1115/gt2022-82502
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Assessment of Turbine Center Frames and Turbine Vane Frames Under the Influence of Purge Flows

Abstract: This paper investigates and compares the aerodynamics of two state-of-the-art configurations for the intermediate turbine duct (ITD) in a turbofan engine: the turbine center frame (TCF), which is typical of conventional dual-spool engines and features symmetric aerodynamic strut fairings, and the turbine vane frame (TVF), which integrates a set of turning struts and splitters directly in the duct, thus enabling length and weight benefits at engine system level. The measurement data utilized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While the investigated radial positions show comparable amplitudes at the 𝐵𝑃𝐹, the outermost sensor (𝑥 = 1, outside of the stator seal lip) always measures the highest magnitude at the 𝐵𝑃𝐹 multiples. A minor peak is spotted at 𝑓 ≈ 0.63 ⋅ 𝐵𝑃𝐹, which corresponds to a linear combination of the HPT and LPT blade passing frequencies: Merli et al [34] also found…”
Section: Time-resolved Pressure Measurements Inside the Dhcmentioning
confidence: 91%
See 1 more Smart Citation
“…While the investigated radial positions show comparable amplitudes at the 𝐵𝑃𝐹, the outermost sensor (𝑥 = 1, outside of the stator seal lip) always measures the highest magnitude at the 𝐵𝑃𝐹 multiples. A minor peak is spotted at 𝑓 ≈ 0.63 ⋅ 𝐵𝑃𝐹, which corresponds to a linear combination of the HPT and LPT blade passing frequencies: Merli et al [34] also found…”
Section: Time-resolved Pressure Measurements Inside the Dhcmentioning
confidence: 91%
“…While the investigated radial positions show comparable amplitudes at the BPF, the outermost sensor (x = 1, outside of the stator seal lip) always measures the highest magnitude at the BPF multiples. A minor peak is spotted at f ≈ 0.63 • BPF, which corresponds to a linear combination of the HPT and LPT blade passing frequencies: Merli et al [34] also found pressure fluctuations with the mentioned periodicity in the annulus, upstream of the TVF struts. No non-synchronous components, which could be associated with rotating flow modes [18], are detected with the current measurement setup, at least not in the same order of magnitude as the BPF-related components.…”
Section: Time-resolved Pressure Measurements Inside the Dhcmentioning
confidence: 95%
“…There are very few works available involving more or different cavities than the upstream hub one; for instance, Zlatinov et al [8] numerically studied the effect of the upstream shroud purge injection, concluding that it was partially recovering the associated losses by inhibiting the tip leakage flow. Also, Merli et al [9] experimentally investigated the total pressure loss across intermediate turbine ducts, varying the injection rates in a fully purged HPT stage. A thorough review of the open literature yielded no publications regarding the performance of a fully purged HPT stage.…”
Section: Introductionmentioning
confidence: 99%